A survey to explore the current use of injection therapy as part of a conservative treatment plan for degenerative meniscal lesions within UK based, injection trained physiotherapy members of the society of musculoskeletal medicine. (2nd April 2016) - Arithoppah, Rikesh; Caldwell, Kay; Smith, Gordon
Abstract : Objectives : To explore the current use of injection therapy as part of a conservative treatment plan for degenerative meniscal lesions (DML) within UK based physiotherapy members of the Society of Musculoskeletal Medicine (SOMM) with injection training. Methods : An online survey was distributed via email to all UK based, SOMM physiotherapists who had trained and received their injection diploma through the SOMM ( n = 203) with a response rate of 32% ( n = 64). The data were analysed using descriptive statistics, contingency tables and the Fisher's exact test. A P value ≤0.05 was considered significant. Ethical clearance was gained through the SOMM and Middlesex University. Results : Of the respondents 98% ( n = 62) of current UK based, injection trained SOMM physiotherapists utilize conservative treatment for DML of which 81% ( n = 52) include injection therapy. Seventy-seven per cent ( n = 49) who currently use injection therapy for DML administer a combination of 40 mg Depomedrone combined with local anaesthetic via a patellofemoral approach. Those not using injection therapy as part of their management of DML attributed this to local department restrictions and lack of evidence. Discussion : This research has helped further understand the use of injection therapy for DML and where it fits within a conservative treatment plan. The benefit from injection therapy reported by respondents is similar to previous research but could be influenced by injection exposure and potentially steroid choice. Overall a consensus is starting to appear regarding dosage, steroid, and administration; however, differences arise when comparing individual department guidelines to CSP and NICE guidelines.